Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1109/jstsp.2012.2211996
|View full text |Cite
|
Sign up to set email alerts
|

Image Retargeting Quality Assessment: A Study of Subjective Scores and Objective Metrics

Abstract: Abstract-This paper presents the result of a recent large-scale subjective study of image retargeting quality on a collection of images generated by several representative image retargeting methods. Owning to many approaches to image retargeting that have been developed, there is a need for a diverse independent public database of the retargeted images and the corresponding subjective scores to be freely available. We build an image retargeting quality database, in which 171 retargeted images (obtained from 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 39 publications
0
62
0
Order By: Relevance
“…In Rubinstein's study [19], the authors used some objective distance metrics, such as bi-directional similarity [20], color layout descriptor [21], BDW [17], edge histogram [22], SIFTflow [23], and Earth-Mover's Distance [24], then estimated how well the objective metrics agree with the users' subjective preferences. Ma et al [25] conducted similar experiments. These two studies showed that the performances of the objective quality metrics for retargeted images are still not good enough.…”
Section: Related Workmentioning
confidence: 83%
“…In Rubinstein's study [19], the authors used some objective distance metrics, such as bi-directional similarity [20], color layout descriptor [21], BDW [17], edge histogram [22], SIFTflow [23], and Earth-Mover's Distance [24], then estimated how well the objective metrics agree with the users' subjective preferences. Ma et al [25] conducted similar experiments. These two studies showed that the performances of the objective quality metrics for retargeted images are still not good enough.…”
Section: Related Workmentioning
confidence: 83%
“…In this experiment, the accuracy of the full reference image quality metric by using the dataset RetargetMe dataset [8] database and NRID database [7] is evaluated. The sample images from RetargetMe database are shown in Fig 3. For this dataset we have compared all the eight retargeted schemes used in [8].…”
Section: Resultsmentioning
confidence: 99%
“…It is the first in-depth perceptual study with a large number of users for image retargeting quality assessment. A different subjective study was proposed in [16], in which the user evaluation was carried out by simultaneous double stimulus for continuous evaluation [1] that scored only one retargeted image each time rather than pairwise comparison. Castillo et al [3] developed an image retargeting survey using eye tracking technology.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, an aspect ratio similarity (ARS) metric [33] was proposed, which characterizes how the source image is resized into the target image by geometric changes and provides an efficient solution based on a Markov random field. Noting that human judgment of retargeting quality often involves multiple factors, several state-of-the-art methods combine several metrics that characterize different factors of image retargeting quality [16,17,12].…”
Section: Related Workmentioning
confidence: 99%